2018
DOI: 10.1155/2018/4313610
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Dentistry: Types of Intra- and Extraoral Tissue-Derived Stem Cells and Clinical Applications

Abstract: Stem cells are undifferentiated cells, capable of renewing themselves, with the capacity to produce different cell types to regenerate missing tissues and treat diseases. Oral facial tissues have been identified as a source and therapeutic target for stem cells with clinical interest in dentistry. This narrative review report targets on the several extraoral- and intraoral-derived stem cells that can be applied in dentistry. In addition, stem cell origins are suggested in what concerns their ability to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 155 publications
0
45
0
Order By: Relevance
“…They can differentiate into almost all specific lines. Whereas, ASCs are typically categorized as non-pluripotent cells, instead, as multipotent stem cells that exist in few numbers within adult tissues and are responsible for maintaining tissues healthy and repairing damages by self-regeneration and differentiation into specific cell types (Paz et al, 2018[ 107 ]). ASCs are also known as somatic stem cells or postnatal stem cells and can be isolated from various adult organs, including bone, muscle, skin, nerve, pancreas, heart, and dental tissues (Mahla, 2016[ 74 ]).…”
Section: Stem Cell Types and Sourcesmentioning
confidence: 99%
“…They can differentiate into almost all specific lines. Whereas, ASCs are typically categorized as non-pluripotent cells, instead, as multipotent stem cells that exist in few numbers within adult tissues and are responsible for maintaining tissues healthy and repairing damages by self-regeneration and differentiation into specific cell types (Paz et al, 2018[ 107 ]). ASCs are also known as somatic stem cells or postnatal stem cells and can be isolated from various adult organs, including bone, muscle, skin, nerve, pancreas, heart, and dental tissues (Mahla, 2016[ 74 ]).…”
Section: Stem Cell Types and Sourcesmentioning
confidence: 99%
“…Stem cells play vital roles in the repair of every tissue of the organism. They are undifferentiated cells, capable of renewing themselves and, by differentiation, they can be induced to develop into many different cell lineages [ 185 ]. They have been proved to be promising in tissue regeneration, as well as in the augmentation process.…”
Section: Tissue Engineering-stem Cell Application In Bone Augmentamentioning
confidence: 99%
“…It includes key elements like extracellular matrix scaffolds and stem cells [ 192 ]. Furthermore, clinical trials about jaw bone regeneration applied in dental areas have demonstrated positive results [ 185 ].…”
Section: Tissue Engineering-stem Cell Application In Bone Augmentamentioning
confidence: 99%
“…Alveolar bone loss is a chronic disease affecting millions of people worldwide, which characterized by osteoporosis, stricken bone strength, and bone tissue degeneration (Paz, Maghaireh, & Mangano, ). There are multiple factors that can lead to alveolar bone resorption, such as tooth extraction or loss due to severe cavities, trauma, root fracture, or periodontal diseases; injury; inflammation; and osteoporosis (Zhang, Wei, Miron, Zhang, & Bian, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell studies are an up and coming way to mimic physiological processes in osteogenesis and may offer new insight into the fundamental molecular mechanisms. Bone marrow mesenchymal stem cells (BMSCs), which is a multipotential differentiation cell type presented in adult bone marrow, are used most extensively in bone regeneration studies (Paz et al, ). However, the harvest procedure of BMSCs is invasively, and their potency is decreased easily because of age and diseases.…”
Section: Introductionmentioning
confidence: 99%